COMPOSITION OF AMINO ACID HYDROLYZATE PROTEIN FROM SEA CUCUMBERS (Paracaudina australis) WITH THE ADDITION OF THE ENZYME ALKALASE - Antonius Zulqaiman; Rahman Karnila; Mery Sukmiwati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
ABSTRACT Berunok sea cucumber is one of the typical marine biota on Karimun Island that has not been utilized optimally, even though the berunok sea cucumber has a high protein content, which is 6-70% in dry conditions, and is thought to be composed of several specific amino acids. Therefore, the sea cucumber has the potential to be used as a raw material for protein hydrolyzate. The hydrolysis process in the manufacture of hydrolysates more often uses enzymes, because it is safer and more profitable, one of which is the alkalase enzyme. This study aims to determine the composition of amino acids contained in the hydrolyzed sea cucumber protein with alkalase added. The research method used is experimental by conducting a series of experiments. This research consisted of 3 stages, namely: 1) making sea cucumber flour, 2) making protein hydrolyzate, and 3) amino acid analysis. Parameter analysis of this study is the analysis of amino acids. The results showed that the hydrolyzed sea cucumber protein with alkalase added to 17 types of amino acids, consisting of 9 essential amino acids and 8 non-essential amino acids. Keywords: berunok sea cucumber, protein hydrolyzate, alkalase enzyme, amino acid